ENGAGEMENT IN DAILY ACTIVITIES AMONG PEOPLE TRANSITIONING FROM WORK TO RETIREMENT IN MALAYSIAN PERSPECTIVE - Harnisha Haidhir; Akehsan Dahlan (Journal of Islamic, Social, Economics and Development, 2021)
The transition from work to retirement is a natural yet complex process for an individual that involved adjustment in several aspects of life. These adjustments involve the Instrumental of Daily Activities (IADL), work-related, leisure, and social activities. However, the information related to these areas is still unclear in Malaysia. Therefore, there is a need to conduct this study among the pre-retirement and retired groups. This study aims to identify the pattern of the activity engagement between these two groups based on IADL, leisure, social, and work-related activities domains. A cross-sectional study was conducted using the Malay version of the Occupational Gaps Questionnaire (OGQ-M). A total of 598 respondents aged 55 to 64 years old lived in the community in Malaysia involved in this study. The results show there was a statistically significant difference in the occupational engagement in leisure (p<0.05), social (p<0.01), work-related (p<0.01), and total occupational engagement between these two groups (p<0.01). In conclusion, there is a great potential of the OT profession to assist the people in transition to retirement by assessing their preferred activities engagement to identify their potential, develop interest, design and implement suitable pre-retirement planning program in Malaysia.